The Popularity of Outcome Measures Used in the Foot and Ankle Literature. Issue 1 (February 2020) - Hijji, Fady Y.; Schneider, Andrew D.; Pyper, Michael; Laughlin, Richard T.
Background. Outcome measures are frequently employed in clinical studies to determine the efficacy of orthopaedic surgical procedures. However, substantial variability exists among the outcome instruments utilized in foot and ankle (F&A) literature. The purpose of this study is to determine the number of outcome measures reported in F&A literature recently published in major orthopaedic journals and the association between study characteristics and the use of particular outcome measurement categories.Methods. All manuscripts published in 6 major orthopaedic journals between 2013-2017 reporting at least one clinical outcome measure were collected. For each manuscript, the journal, title, authors, country/region of origin, level of evidence, topic, and anatomic location were recorded. Outcome measures were characterized as generic, F&A specific, and disease specific. Poisson regression with robust error variance was used to test for association between study characteristics and outcome measure categories.Results. A total of 541 F&A articles were included with fifty-two different outcome measures reported. The most popular tool was the American Orthopaedic Foot and Ankle Score (AOFAS) (56.9%). Generic outcome measures were used in 331 (61.1%) studies, while 440 (81.3%) studies used F&A specific measures and 64 (11.8%) used disease-specific measures. The use of generic and disease-specific outcome measures was associated with a higher level of evidence (p < 0.001).Conclusion. AA substantial variety of outcome measures are employed among recent published studies, with many studies utilizing non-validated measures. Reporting a combination of validated and focused outcome measures is necessary to improve the quality and generalizability of published studies in foot and ankle literature. Levels of Evidence: Level II: Systematic review